THE EFFORTS TO INCREASE STUDENT ACTIVITY IN MATH LEARNING WITH SNOWBALL THROWING MODEL IN STUDENTS CLASS VIII - Siti Sholihah; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
The activity of students when lessons in class are still lacking. Some of his students still consider mathematics a difficult subject to understand. The students tend to be passive when the lesson takes place; they just sit back and accept the material presented by the teacher. This study aims to improve students' activeness in learning mathematics using Snowball Throwing (ST) model. This study is a classroom action research consisting of two cycles. The subject of this research is the students of class VIII C SMP Muhammadiyah 3 Yogyakarta academic year 2016/2017. This research aims to increase student activeness in learning mathematics by using the Snowball Throwing model. Data collection techniques include observation, unstructured interviews, and diagnostic tests. The success criterion in this research is marked by the increase in the average student activity percentage of at least 61% or good. The results showed that using the model learning model of Snowball Throwing can improve students' activity in learning mathematics. This is seen as an increase in the percentage of student's activity is 56.32% with sufficient criteria in cycle I and increased in the second cycle of 71.75% with Good criteria.